Redox-active molecules as organocatalysts for selective oxidative transformations – an unperceived organocatalysis field - Lopat’eva, Elena R.; Krylov, Igor B.; Lapshin, Dmitry A.; Terent’ev, Alexander O. (Beilstein Journal of Organic Chemistry, 2022)
Organocatalysis is widely recognized as a key synthetic methodology in organic chemistry. It allows chemists to avoid the use of precious and (or) toxic metals by taking advantage of the catalytic activity of small and synthetically available molecules. Today, the term organocatalysis is mainly associated with redox-neutral asymmetric catalysis of C–C bond-forming processes, such as aldol reactions, Michael reactions, cycloaddition reactions, etc. Organophotoredox catalysis has emerged recently as another important catalysis type which has gained much attention and has been quite well-reviewed. At the same time, there are a significant number of other processes, especially oxidative, catalyzed by redox-active organic molecules in the ground state (without light excitation). Unfortunately, many of such processes are not associated in the literature with the organocatalysis field and thus many achievements are not fully consolidated and systematized. The present article is aimed at overviewing the current state-of-art and perspectives of oxidative organocatalysis by redox-active molecules with the emphasis on challenging chemo-, regio- and stereoselective CH-functionalization processes. The catalytic systems based on N-oxyl radicals, amines, thiols, oxaziridines, ketone/peroxide, quinones, and iodine(I/III) compounds are the most developed catalyst types which are covered here.
Keywords: CH-functionalization; free radicals; hypervalent iodine; N-oxyl radicals; redox-active molecules